The role of female leadership and female entrepreneurship in business in Surabaya - Liliani Liliani; Christian Budiman Urbanus (Universitas Hayam Wuruk Perbanas, 2014)
The issue of gender equality has still been a global topic. This implies that male and female should be treated equally. In Indonesia, the realization of gender equality should be pursued by providing wider opportunities for females in various aspects such as in social life with their role in the economy. Nowadays, females can freely open businesses or become entrepreneurs, and even they have opportunity to lead an organization. However, in reality, the number of business females is still very limitedcompared to the males. For that reason, it requires empowering the female for increasing the number of female entrepreneurs in Indonesia. This study provides a typical character of leadership and entrepreneurship of females in running the business. It explores the role of leadership and entrepreneurship of female in business in Surabaya. This is qualitative methods of case study, with in-depth interviews on the informants of female entrepreneurs who have business in Surabaya. It shows that female’s leadership in business applies transformational and transactional leadership style. Yet, they tend to act as a controller while the role as an enabler is done only for certain conditions. From the entrepreneurship point of view, it shows an important role of entrepreneurship that is to build a culture of innovation and create competitiveness.